Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.cortex.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal mediation of the reading network predicts intervention response in dyslexia

Abstract: A primary challenge facing the development of interventions for dyslexia is identifying effective predictors of intervention response. While behavioral literature has identified core cognitive characteristics of response, the distinction of reading versus executive cognitive contributions to response profiles remains unclear, due in part to the difficulty of segregating these constructs using behavioral outputs. In the current study we used functional neuroimaging to piece apart the mechanisms of how/whether e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 70 publications
(99 reference statements)
3
32
0
Order By: Relevance
“…Based on behavioral studies of genre, we propose that the FPN may specifically be involved in facilitating goal-directed comprehension processes in the DMN during reading, and this facilitation is in greater demand during expository comprehension. These results both enhance and are consistent with previous work that indicates the FPN may act to assist task-specific networks through goal-directed, top-down mediation processes, resulting in better clinical and learning outcomes (Cole et al 2013(Cole et al , 2014Aboud et al 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Based on behavioral studies of genre, we propose that the FPN may specifically be involved in facilitating goal-directed comprehension processes in the DMN during reading, and this facilitation is in greater demand during expository comprehension. These results both enhance and are consistent with previous work that indicates the FPN may act to assist task-specific networks through goal-directed, top-down mediation processes, resulting in better clinical and learning outcomes (Cole et al 2013(Cole et al , 2014Aboud et al 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Both theories connect the FPN to the strategic integration processes referenced in the Landscape Model that are necessary for the integration of background information. Additional work suggests that the FPN is a top-down neural scaffold that supports the functions of other brain systems across a range of cognitive skills and clinical populations (Cole et al 2014), including reading specifically (Aboud et al 2016(Aboud et al , 2018. Consequently, a number of studies suggest that the FPN is a top-down network that, in the context of reading, may assist in strategic processing.…”
Section: Neurobiological Processes Involved In Comprehensionmentioning
confidence: 99%
“…Activation of some of these regions also predicted a positive intervention response (Nugiel et al., ). As such, the findings are consistent with a recent study (Aboud, Barquero, & Cutting, ) that found that activation of both reading and cognitive control regions during a lexical decision task predicted intervention response in a group defined with poor decoding. Our groups were identified largely by poor decoding fluency and reading comprehension, showing convergence not only in struggling readers defined with different criteria, but also across single word and sentence‐level fMRI tasks.…”
Section: Discussionsupporting
confidence: 90%
“…Our groups were identified largely by poor decoding fluency and reading comprehension, showing convergence not only in struggling readers defined with different criteria, but also across single word and sentence‐level fMRI tasks. While Aboud and colleagues did not have a nonlexical EF task in their study, they proposed that the interaction of brain regions involved in EF and reading tasks was necessary for a positive intervention response (Aboud et al., ). Our studies support this proposal, but add a critical specification: these EF activation differences in struggling and typical readers may be limited to the context of reading.…”
Section: Discussionmentioning
confidence: 99%
“…Despite new data from neuroscience and cognitive science research about neurobiological predictors of literacy intervention treatment response (Aboud et al, 2018), not much has changed in the ways that we teach children with dyslexia to read. Landi et al (2019) reiterate that closing the gap between what we know and how to use that information remains a broad goal for delivering on the purpose of using neuroscience to guide literacy instruction.…”
Section: Dyslexiamentioning
confidence: 99%